Meta-analysis study on anesthetic sedation recovery and onset times in pediatric and elderly patients undergoing CT and MRI - Qiong Zhao; Fei Meng; Huimei Han; Lili Han (Biomedical Papers)
Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are crucial diagnostic modalities that require patients to remain immobile for extended periods, with anesthesia sometimes used for comfort and image quality enhancement. The study compares dexmedetomidine and propofol in reducing recovery time and sedation onset in pediatric and elderly patients undergoing CT and MRI procedures. A meta-analysis of fifteen studies assessing recovery time, sedation onset, and failed sedation between dexmedetomidine and propofol in pediatric and elderly patients during CT and MRI was conducted. The study indicated that the administration of anaesthesia markedly improved patient compliance and reduced motion artefacts in both CT and MRI (P<0.00001, I2=94%). The meta-analysis indicated that the mean difference (MD) in the onset of sedation was significantly faster in the control group (P<0.00001, I2=96%). The study reveals that dexmedetomidine and propofol anesthesia can improve patient image quality during CT and MRI procedures by reducing motion artefacts. Dexmedetomidine sedated people more quickly than propofol, but no significant differences in sedation duration were observed.